Symptom Experience and Perceived Health Status of People With Long COVID in Thailand - Bangern Pumipak MS, RN; Sirinapha Jittimanee PhD, MSN, MPH, RN; Sirima Thananun RN; Kaewjai Mathong MS, BPH; Jomtien Poungdok BSW; Manthana Sinsap MPH, BPH; Thatsanee Sueathong BSc; Oranong Kongruang MSc, BSc; Sujitraporn Faungprachakorn MPH, BSc; Thunyarut Thunyaphun PharmD; Poramate Insook MNS, RN; Kaewalee Soontornmon PhD, MS, MD (SAGE Open Nursing, 2023)
Introduction Despite the World Health Organization declaring COVID-19 no longer a public health emergency, reports of long COVID persist globally, raising concerns about its impact on individuals. Objective This retrospective study aimed to explore the symptom experiences of individuals with long COVID-19 and examine the relationship between those experiences and perceived negative health status in Thailand. Methods The study focused on individuals with moderate to severe COVID-19 infections. Between July 3, 2022 and December 1, 2022, we conducted telephone interviews with 86 individuals who tested positive for SARS-CoV-2 and received outpatient care in Bangkok. The COVID-19 Yorkshire Rehabilitation Screening was utilized to measure symptom occurrence, duration, severity, and health status on an 11-point numerical rating scale from 0 (none or excellent) to 10 (the worst). A Spearman rank correlation was used to analyze the relationships between long COVID symptoms and negative perception of health status. Results Among the participants, 75.6% had long COVID, with a median of three symptoms lasting for a median duration of 5.6 months. Difficulties in performing daily activities were most common, reported by 50.8% of participants. The majority (80.0%) experienced itching, headache, cognition, muscle pain, continence, and sleeping problem for 6 months. Loss of taste was the most severe symptom, with a mean severity rating of 8.8. There were significant positive relations between a negative perception of health status and multiple symptoms, symptom severity, functional disability, and additional symptoms. Conclusion Individuals with moderate to severe COVID-19 infection who experienced long COVID had poorer perceived health status. To effectively manage and improve the health status of individuals with long COVID, nurses should provide follow-up care, assess not only the occurrence of symptoms but also their duration and severity, and evaluate performance outcomes.